Jordan: a case study of the relationship between Islamic finance and Islamist politics / Wan Noor Hazlina Wan Jusoh - Wan Jusoh, Wan Noor Hazlina (2012)
Islamist politics in Jordan are very much influenced by the Muslim Brotherhood (Schanzer, 2011). The Muslim Brotherhood or also known as Ikhwan al-Muslimin is the world's oldest, largest and most influential Islamist organization (Leiken & Brooke, 2007) which was founded by Hassan al-Banna in 1928. Initially, this Islamic reform organization began as a movement for the reform of the individual and social morality; however its broader political significance grew to challenge secular leadership in Muslim societies. Its strategy of change was to facilitate a more Muslim society through grassroots programs in education, charity, and social activities. Over time, branches of the Muslim Brotherhood were founded in other Arab countries, including Jordan in 1945 (Wiktorowicz, 1999). Since then, the Muslim Brotherhood has played a significant role in the socio-politics of Jordan until it brought to the formation of Islamic Action Front Party in 1993 as a new name to the Jordan Muslim Brotherhood's political wing (Schanzer, 2011). Simultaneously, Muslim Brotherhood also has penetrated many Jordanian Islamist leaders' and intellectuals' mind regarding the concept of Islamic economics and the establishment of Islamic financial institutions in Jordan.